Elucidating a fresh perspective on the interplay between exosomes and rheumatoid arthritis - Zhao, Jianan; Zhang, Binbin; Meng, Wanting; Hu, Jing (Frontiers in Cell and Developmental Biology, 2023)
Rheumatoid arthritis (RA) is a chronic autoimmune disease characterized by chronic synovitis and the destruction of bones and joints. Exosomes are nanoscale lipid membrane vesicles originating from multivesicular bodies and are used as a vital means of intercellular communication. Both exosomes and the microbial community are essential in RA pathogenesis. Multiple types of exosomes from different origins have been demonstrated to have effects on various immune cells through distinct mechanisms in RA, which depend on the specific cargo carried by the exosomes. Tens of thousands of microorganisms exist in the human intestinal system. Microorganisms exert various physiological and pathological effects on the host directly or through their metabolites. Gut microbe-derived exosomes are being studied in the field of liver disease; however, information on their role in the context of RA is still limited. Gut microbe-derived exosomes may enhance autoimmunity by altering intestinal permeability and transporting cargo to the extraintestinal system. Therefore, we performed a comprehensive literature review on the latest progress on exosomes in RA and provided an outlook on the potential role of microbe-derived exosomes as emerging players in clinical and translational research on RA. This review aimed to provide a theoretical basis for developing new clinical targets for RA therapy.